Characterization of selective quantum well intermixing in 1.3 mu m GaInNAs/GaAs structures - Sun, Handong (2009)
Rapid thermal annealing combined with SiO2 caps deposited on the surface of samples by different techniques is used to selectively disorder 1.3 mum GaInNAs/GaAs multiquantum wells which have been preannealed in situ to the stage of blueshift saturation. After thermal annealing under specific conditions, a shift in band gap of over 170 meV has been obtained in sputtered SiO2-capped samples, while uncapped and plasma enhanced chemical vapor deposited SiO2-capped samples demonstrated a negligible shift. Quantum well intermixing in sputtered SiO2-capped samples originates from enhanced compositional interdiffusion due to the generation of point defects by ion bombardment during the sputtering process. Secondary ion mass spectrometry has confirmed that the enhanced blueshift was caused by the interdiffusion of group III atoms (In and Ga) between the quantum wells and barriers. Detailed photoluminescence and excitation spectroscopy were performed to study the optical properties of both intermixed and nonintermixed samples.